2023
DOI: 10.7759/cureus.36920
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Social Challenges Parents of Children With Strabismus Face in Qassim Region, Saudi Arabia: A Cross-Sectional Study

Abstract: Strabismus or squint is when one eye is misaligned or looking in a different direction. Some people consider strabismus as a cosmetic problem, causing patients in this condition to be mishandled, especially children, which might affect their vision and their quality of life. This study aimed to evaluate the psychological and social challenges faced by parents of children with strabismus during the years 2020-2021. Subjects and methodsThis is a cross-sectional study conducted among parents who have children wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Children hold a special place in the hearts of their parents, so witnessing their child in distress can have a profound emotional impact on the parent. Althiabi et al [32] found that mothers of children with strabismus experienced higher levels of psychological impact compared to fathers. In Taiwanese society, mothers may require additional support, as they often bear the primary responsibility for child healthcare and medical assistance, in uenced by traditional gender roles [33].…”
Section: Discussionmentioning
confidence: 99%
“…Children hold a special place in the hearts of their parents, so witnessing their child in distress can have a profound emotional impact on the parent. Althiabi et al [32] found that mothers of children with strabismus experienced higher levels of psychological impact compared to fathers. In Taiwanese society, mothers may require additional support, as they often bear the primary responsibility for child healthcare and medical assistance, in uenced by traditional gender roles [33].…”
Section: Discussionmentioning
confidence: 99%